Aspectos da regulação sobre o ensino a distância no Brasil - Caram, Nirave Reigota [UNESP]; Bizelli, Jose Luis [UNESP] (My University, 2014)
This article presents a reflection on the historical aspects and legislation on Distance Learning (DL). For this, a bibliographic and documentary research was performed with the goal of raising the necessary notes for discussion. The text begins with the characterization of the current society, the Information Society, which supports the modern distance education, which uses information and communication technologies (ICTs) to establish the process of learning teaching. Five stages of the EAD are identified. Later, the Brazilian legislation concerning the DL is punctuated, starting with the passage by Article 80 of the Guidelines and Bases Law-LBD (Law 9394/96) along with the critical analysis of Decree 5,622/05. Finally, in the final considerations is discussed the negative image that the DL carries by the Brazilian population and obstacles in the existing rules that hinder the democratization of access to education that aims DL.

O presente artigo apresenta uma reflexão em torno dos aspectos históricos e de legislação sobre Ensino a Distância (EAD). Para tanto, foi realizada uma investigação bibliográfica e documental com o objetivo de levantar os apontamentos necessários para a discussão. O texto inicia-se com a caracterização da sociedade atual, a Sociedade da Informação, que ampara o EAD moderna, a qual utiliza as tecnologias de informação e comunicação (TIC) para estabelecer o processo de ensino aprendizagem. Cinco fases do EAD são identificadas. Posteriormente, a legislação brasileira referente ao EAD é pontuada, iniciando com a passagem pelo Art. 80 da Lei de Diretrizes e Bases–LBD (Lei 9394/96) juntamente com a análise crítica do Decreto 5.622/05. Por fim, nas considerações finais é discutida a imagem negativa que o EAD carrega por parte da população brasileira e entraves nas normas vigentes que dificultam a democratização do acesso à Educação que o EAD objetiva.
Keywords: Distance Education; History of DL; DL legislation; Education Democratization; Ensino a Distância; História do EAD; Legislação do EAD; Democratização da Educação